Market Selection and Asymmetric Information - Mailath, George J.; Sandroni, Alvaro (Review of Economic Studies, 2003)
We consider a dynamic general equilibrium asset pricing model with heterogeneous agents and asymmetric information. We show how agents' different methods of gathering information affect their chances of survival in the market depending upon the nature of the information and the level of noise in the economy.